Pengaruh Model Pembelajaran Inkuiri Terbimbing dengan Leaflet 3D terhadap Motivasi dan Berpikir Logis Siswa Kelas VII MTSN 2 Mataram - Usnah Meilani; Suhirman; Firman Rahman (Bioindikator: Jurnal Biologi dan Pendidikan Biologi, 2024)
This study aims to evaluate the impact of using a guided inquiry learning model supported by 3D leaflet media on the learning motivation and logical thinking skills of seventh-grade students at MTsN 2 Mataram. The research method applied is a quasi-experiment with a non-equivalent control group design. The research sample consists of two classes: class VII C as the experimental group implementing the guided inquiry model with the aid of 3D leaflets, and class VII B as the control group using conventional learning methods. The research instruments include a learning motivation questionnaire in the form of an observation sheet and a logical thinking skills test consisting of a pretest and posttest. The results indicate a significant increase in the learning motivation and logical thinking skills of students in the experimental class compared to the control class. The use of 3D leaflet media has proven effective in supporting the guided inquiry learning process, making it an alternative learning strategy that can enhance the quality of education. These findings are expected to contribute positively to the development of innovative and interactive learning models at the secondary school level.